SENI PANTUN GIRIWANGI KI AKIS - Agus Setyawan (Pascasarjana Institut Seni Indonesia Surakarta, 2009)
The results of the research showed that the art of Pantun Giriwangi Ki Akis is an art form which is closed related to the ritual ceremonies held regularly by the community of Baros village in the Arjasari district of Bandung. In performance, the structure of this art form includes the preparation of offerings, the reading of a prayer, the recitation of a kind of magical spell or incantation, and other elements known as pangambatan, bangbalikan, and mangkat lakon, or the presentation of the story. The function of this kind of performance is as a rice ceremony (known as netepken Ibu), an expression of thanks, or an exorcism ritual. The symbolic meaning contained in the performance reflects the way of life, traditions, and cus- toms of the local community. This research aims to explain the form, function, and symbolic meaning of Pantun Giriwangi Ki Akis, contained in the story of Mundinglaya Dikusumah. An analytical descriptive method was used for the study. This method is a procedure used to solve a problem by describing the object of the research based on the data collected, and then carrying out an accurate analysis of the data.The data for the research was collected using a bibliographical study, including a study of various literature and audio-visual recordings. The main activity of the study was to watch a recording of a performance and then attempt to identify which were the important parts of the performance to be studied and analysed in more depth. Additional data was collected through interviews and documentation. The art of Pantun Giriwangi Ki Akis is closely related to the ritual ceremonies held regularly by the community of Baros village in the Arjasari dis- trict of Bandung. This is of great importance since the community believes that by performing Pantun as a part of these ritual ceremonies, their lives will become better. The art of Pantun Giriwangi Ki Akis contains a number of symbolic mean- ings which set a good example to follow and can be used as a foundation on which people can base their lives. Keywords: Pantun Giriwangi Ki Akis, form, function, symbolic meaning